Seamanship techniques for shipboard & maritime operations - House, D. J. (Oxford : Elsevier Butterworth-Heinemann, 2004)
This third edition presents the most thorough revision of Seamanship Techniques since first publication in 1987. Already recognised as one of the leading texts for cadet and serving seafarers of all ranks, this new edition covers all the seamanship knowledge required by students and experienced seafarers alike. Ideal for Merchant Navy Officers from Cadet rank to Master Mariner, the new edition incorporates the 2003 amendments to the Collision Avoidance Regulations and new material covering regulations and practice on cargo operations, survival systems, GMDSS requirements, watch keeping duties, rescue operations and pollution control, to name a few. Used by training establishments around the world this is the only reference to both shipboard practice and ship operations that seafarers will need. * Well-established, well-known, well-liked, well-trusted; the fully comrehensive seamanship reference Covers all the knowledge required to take readers from Cadet to Master rank * Includes the 2003 revision to the Collision Avoidance Rules and fully aligned with the IMO STCW (Standards of Training, Certification and Watchkeeping) requirements.
The ship -- Anchor work (fundamentals) -- Ropework -- Wirework and rigging -- Lifting gear -- Cargo and hatchwork -- Boatwork and life saving appliances -- Survival craft and practice -- Communications -- Watchkeeping duties -- Marine instruments monitoring and measurement -- Meteorology -- Preventing collisions at sea -- Emergencies -- Fire-fighting -- Search and rescue operations -- Ship-handling -- equipment -- Ship-handling -- manoeuvring and mooring operations -- Tanker operations -- The application of MARPOL and the prevention of pollution.
Includes index.
Keywords: Seamanship -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc